Effective Learning Strategies: Applying the Articulation Model in Teaching and Learning Activities - Moch Tohet; Zaenol Fajri; Rifa Muslihatin Nufus (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to examine the impact of implementing the articulation model on students’ speaking skills at Madrasah Aliyah Islamiyah Syafi'iyah, Paiton, Probolinggo. The articulation model is an innovative approach that encourages students to actively retell the material they have learned to their peers. This method is designed to enhance students' comprehension, improve their communication skills, and boost their confidence. Methodology: This research employed a quantitative approach with an experimental design, involving two groups: an experimental group taught using the articulation model and a control group taught using conventional teaching methods. Main Findings: The findings indicate that students taught using the articulation model demonstrated a significant improvement in their speaking skills, with 85% able to deliver material coherently, logically, and confidently. Additionally, this model enhanced students’ understanding of the subject matter. However, some challenges were observed, such as varying levels of participation among students and difficulties in public speaking, which require specific attention to ensure active engagement for all learners. Novelty/Originality of this study: This study concludes that the articulation model is effective in enhancing students' speaking skills and is applicable at various educational levels, particularly in religious-based learning. Furthermore, the findings highlight the need for teacher training to optimize the implementation of this model and suggest opportunities for further research to explore its application in different educational settings. The study underscores the importance of professional development for educators and the potential for expanding research on this model’s effectiveness across diverse learning environments.